(3ebGdI GdEScfOQ GdEaQhOjiS aj Cf GdbhI GdhGMOI jecf Cf Jchf bGHdI GdCVOGO LejYkG Ydi QCi CQSWhWGdjS GdMcjes - (3GdEScfOQ GdEaQhOjSis
(3ChdgG (B:s
(3bGd GdEScfOQ Ef GQSWhWGdjS PcQ ai cJGHg ai Gdchf hGdaSGO Cf GdbhI GdhGMO jecf Cf Jchf bGHdI ddGVOGO LejYkG s
(3BNQgG (B:s
(3hCeG GdCVOGO adGjecf Cf fchf eYkG GdHJI JeJ GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B17s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(798/17) s
Keywords: (3GdadSaI hGdefWbs